2014
DOI: 10.1103/physrevd.89.036002
|View full text |Cite
|
Sign up to set email alerts
|

Limits on Lorentz andCPTviolation from double beta decay

Abstract: Deviations from Lorentz and CPT invariance in the neutrino sector and their observable effects in double beta decay are studied. For two-neutrino double beta decay, a spectral distortion and its properties are characterized for different isotopes. Majorana couplings for Lorentz violation are studied and shown to trigger neutrinoless double beta decay even for negligible Majorana mass. Existing data are used to obtain first limits of 5 × 10 −9 for 18 individual coefficients and attainable sensitivities in curre… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
62
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(63 citation statements)
references
References 83 publications
1
62
0
Order By: Relevance
“…ofq ) [30]. This deviation in the neutrino momentum modifies the double beta decay transition amplitude as well as the neutrino dispersion relation [30].…”
Section: Analysis Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…ofq ) [30]. This deviation in the neutrino momentum modifies the double beta decay transition amplitude as well as the neutrino dispersion relation [30].…”
Section: Analysis Methodsmentioning
confidence: 99%
“…This deviation in the neutrino momentum modifies the double beta decay transition amplitude as well as the neutrino dispersion relation [30]. This leads to a differential decay rate in terms of the kinetic energies of the two emitted electrons (all energy variables are given in terms of m e ) of…”
Section: Analysis Methodsmentioning
confidence: 99%
“…We remark in passing that other coefficients for Lorentz and CPT violation can produce other novel effects. For instance, CPT-violating Majorana couplings in the SME can trigger neutrinoless double beta decay even for a negligible Majorana mass [69].…”
Section: Oscillation-free Signalsmentioning
confidence: 99%
“…The particular coefficient that produces isotropic effects can be studied by searching for modifications in the full beta spectrum of neutron decay [66,67]. A similar distortion of the full spectrum appears in the two-neutrino mode of double beta decay experiments [69]. This alteration of the electron-sum spectrum in two-neutrino double beta decay has been explored by the EXO-200 experiment, obtaining the first experimental limit on the relevant coefficient for CPT-odd Lorentz violation [70].…”
Section: Oscillation-free Signalsmentioning
confidence: 99%
“…Though CPT invariance is in concord with our present theoretical framework of Standard Model of particle physics, it needs to be thoroughly tested experimentally. The literature is replete with many tests for CPT violation, such as in anomalous magnetic moments [55,56], double beta decay [57], some neutral mesons [58][59][60][61][62][63][64][65][66][67][68][69], muon [70,71], neutrino [72][73][74][75][76][77], Higgs boson decay [78], neutron [79], photon [80,81], Hydrogen atom [82], cosmic microwave background measurements [83] as well as some space based experiments [84]. A summary of results of many such studies and more references can be found in Ref [85].…”
mentioning
confidence: 99%